Facial expressions recognising emotions (London : The Sheffield Hallam University, 1998)
The video takes a look at the way facial expressions have evolved and ask how good are we at communicating emotions through our faces. Focusing on the 6 basic emitions : fear, anger, happiness, sadness, suprise and digust
Copy available in CD format
Copy available in DVD format
Acadeis adviser, Mark Coulson
Keywords: Facial expression; Emotions; Expression; Body language